Evolution of tissue and developmental specificity of transcription start sites in Bos taurus indicus - Mehrnush Forutan (Nature Portfolio, 2021)
Forutan et al. measure RNA expression and map transcription start sites (TSSs) between two sub-species of cattle in adult and fetal tissues and demonstrate translocation and changes in TSS distribution between the sub-species. This study provides insight into cattle adaptation and provides support of rapidly evolving TSS between two recently diverged subspecies.